2022
DOI: 10.3920/bm2021.0065
|View full text |Cite
|
Sign up to set email alerts
|

Lacticaseibacillus rhamnosus GG DSM 33156 effects on pathogen defence in the upper respiratory tract: a randomised, double-blind, placebo-controlled paediatric trial

Abstract: Acute upper respiratory tract infections (URTIs) are caused by numerous viruses and bacteria. URTIs can be a cause of morbidity and are among the most common reasons for visiting healthcare practitioners and prescribing antibiotics to children in addition to causing absenteeism from school and work. Oral intake of Lacticaseibacillus rhamnosus GG DSM 33156 has shown beneficial health effects in several clinical trials, primarily relating to immune function and gastrointestinal health in children and adults. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…There were 2 outcomes eligible for analysis. These were (i) duration of episodes ( L rhamnosus GG (27,30,31) and L rhamnosus HN001 (28)) and (ii) number of days of absence ( L rhamnosus GG (27,29,31) and L rhamnosus HN001 (28)). The tests for subgroup differences between the different strains of the same probiotic species showed no statistically significant differences between subgroups ( P = 0.27 for duration of episodes; P = 0.06 for number of days absent) but some heterogeneity ( I 2 = 18.5% and I 2 = 72.8%, respectively) (Figure 7, Supplemental Digital Content, http://links.lww.com/MPG/D27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 2 outcomes eligible for analysis. These were (i) duration of episodes ( L rhamnosus GG (27,30,31) and L rhamnosus HN001 (28)) and (ii) number of days of absence ( L rhamnosus GG (27,29,31) and L rhamnosus HN001 (28)). The tests for subgroup differences between the different strains of the same probiotic species showed no statistically significant differences between subgroups ( P = 0.27 for duration of episodes; P = 0.06 for number of days absent) but some heterogeneity ( I 2 = 18.5% and I 2 = 72.8%, respectively) (Figure 7, Supplemental Digital Content, http://links.lww.com/MPG/D27).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies on respiratory tract infections were included (27)(28)(29)(30)(31). There were 2 outcomes eligible for analysis.…”
Section: Respiratory Tract Infectionsmentioning
confidence: 99%
“…Similar findings were reported in Malaysian children (aged 2 to 6 years) supplemented with Bifidobacterium longum BB536 at a dose of 5 × 10 9 cfu/day for 10 months [ 34 ]. Other studies have shown little or no effect [ 35 36 37 38 ]. Hay et al [ 39 ] reported the duration of URTI on average of 8 days in children in the community.…”
Section: Discussionmentioning
confidence: 99%